2021
DOI: 10.1386/jams_00058_1
|View full text |Cite
|
Sign up to set email alerts
|

Social media, fake news and fake COVID-19 cures in Nigeria

Abstract: This study investigates the impact of social media ‘fake news’ and fake cures headlines on how Netizens viewed and responded to the COVID-19 pandemic in Nigeria. Using data from an online survey (N=254), this study reveals that social media was overwhelmingly the most used type of media for news consumption generally, and the most important source of news about the pandemic. Data further reveal that the impact of extensive exposure to fake news headlines about the pandemic was dangerous and could have a delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
1
9
0
3
Order By: Relevance
“…A study asked whether Americans recall and believe manipulated stories. They found that people who minimally expose themselves to media content, people with less education, and younger people are likely to believe online fake news (Allcott and Gentzkow, 2017;Humprecht, 2019;Uwalaka et al, 2021). The result of this study is similar in some ways to the results of their study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A study asked whether Americans recall and believe manipulated stories. They found that people who minimally expose themselves to media content, people with less education, and younger people are likely to believe online fake news (Allcott and Gentzkow, 2017;Humprecht, 2019;Uwalaka et al, 2021). The result of this study is similar in some ways to the results of their study.…”
Section: Discussionsupporting
confidence: 79%
“…Some of these emerging studies interrogate the relationship between digital networks and fake news related to the COVID-19 pandemic. Some of such studies discovered that the more people make use of social media to receive COVID-19-related information, the more they perceive and behave in a risky manner regarding the virus (Hou et al, 2020;Uwalaka et al, 2021). Studies suggest that citizens of Vietnam accepted as credible, fake news information about COVID-19 than they believed the official information announced by their government (Huynh, 2020).…”
Section: Fake News and Covid-19mentioning
confidence: 99%
“…Studies have shown that many citizens in Northern Nigeria do not believe that Covid-19 exists [10], and many more believe that Covid-19 is a government hoax at further deceiving the population [15]. While much has been published about the disinformation created by some religious leaders, fake news information, political distrust in leadership, and the failure of some parents to permit their wards to take the Covid-19 vaccines [16][17][18], findings in this study has highlighted the need to bridge the Covid-19 vaccine knowledge gap found among 88% of the study population. Many have heard about Covid-19, yet, they still do not have an understanding on how the Covid-19 vaccines were developed and how these could be rapidly approved for public administration without ill intentions on the part of governments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FNI is detrimental to public health and raises several health policy-related issues (Akpan et al, 2021;Al Khaja et al, 2018;Allington et al, 2021;Atehortua and Patino, 2021;Beletsky et al, 2020;Luo and Cheng, 2021;Nazar and Pieters, 2021;Warner et al, 2021). FNI about the prevention and treatment strategies for COVID-19 has lethal consequences (Sridharan and Sivaramakrishnan, 2021;Uwalaka et al, 2021). Propagated FNI is a primary cause of vaccine hesitancy and a reduction in immunisation rates (Basch et al, 2021;Calo et al, 2021;Carrieri et al, 2019;Chen et al, 2021b;Featherstone and Zhang, 2020;Hansen and Schmidtblaicher, 2021;Islam et al, 2021;Romer and Jamieson, 2021;Sallam et al, 2021aSallam et al, , 2021b.…”
Section: Output Of Fnimentioning
confidence: 99%
“…, 2021). FNI about the prevention and treatment strategies for COVID-19 has lethal consequences (Sridharan and Sivaramakrishnan, 2021; Uwalaka et al. , 2021).…”
Section: Literature Analysismentioning
confidence: 99%